A Primer of Absolute Liability - Frank William Miller (Washington University Law Quarterly, 1957)
This Article's purpose is threefold: (1) to provide a basis for judging the significance of fault in the law of torts; (2) to enable the lawyer better to evaluate proposals to expand, contract, or otherwise change the rules in tort cases; (3) to point out recent trends toward an expansion of liability without fault.
Keywords: Strict liability; Liability without fault